2017
DOI: 10.3390/su9081353
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Development Goals: An Experience on Higher Education

Abstract: Sustainable development is acquiring high attendance in higher education. In fact, one of the targets for the Sustainable Development Goals announced by the United Nations in September 2015 aims to ensure that all learners acquire the knowledge and skills needed to promote sustainable development, including, among others, thorough education on sustainable development. The current study focuses on the evaluation of individual works based on the sustainable development suggested to students in a subject of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 19 publications
5
78
1
3
Order By: Relevance
“…In this sense, some experiences have been described; for example, Albareda-Tiana et al analyzed how to develop sustainability competencies in future teachers [68]. The development of works in the field of the Master in Thermal Engineering has been presented by Crespo et al [69]. The Conference of Vice-chancellor of Spanish universities indicated that service-learning could be a tool for the development of sustainability in the university context [32,70].…”
Section: Teaching Methodologymentioning
confidence: 99%
“…In this sense, some experiences have been described; for example, Albareda-Tiana et al analyzed how to develop sustainability competencies in future teachers [68]. The development of works in the field of the Master in Thermal Engineering has been presented by Crespo et al [69]. The Conference of Vice-chancellor of Spanish universities indicated that service-learning could be a tool for the development of sustainability in the university context [32,70].…”
Section: Teaching Methodologymentioning
confidence: 99%
“…It also encompasses efficient energy utilization. Socioeconomic activities that contribute to national economic indicators such as real gross domestic product (GDP), income, employment, manufacturing and retails sales [18] have to take into cognisance an environment that is humanly friendly as captured by the global policy framework called sustainable development goals [19]. This means both the natural environment and social environment [20] have to be protected.…”
Section: Green Computing and Sustainable Developmentmentioning
confidence: 99%
“…By and large, items 1-7-designed as the economic subscale-hung together (Factor 2); this was particularly clear for the Real survey. Additionally, items 8-20-designed as the social (items 8-13) and intellectual (items [14][15][16][17][18][19][20] subscales -hung together fairly cleanly (Factor 1). Items 21-28-designed as the emotional subscale-were split between Factor 1 and Factor 3.…”
Section: Study 2 Resultsmentioning
confidence: 99%